Argh!: An exploration of the response cries of digital game players. Issue 2 (1st June 2013) - Conway, Steven
Response cries are often viewed by an audience as instinctive, asocial and primitive: as simply cathartic release for whatever sensation currently overwhelms the invoker, whether that be the dropping of a phone, stubbing a toe or burning of one's hand. Yet these response cries, as articulated by Erving Goffman, are in many instances also social performances, as the performer attempts to create or sustain a particular impression beneficial to his or her status within a group or larger community. This article focuses upon the response cries of digital game players, discussing what kinds of social meaning are communicated through such shouts and curses, and how they can be productively viewed through the prism of social status, role and gaming capital. In doing so, response cries, though often neglected in analyses of gamers, are shown to be an essential facet of player performance in social contexts, filled with meaning for the attentive analyst.